Pemanfaatan Barang Bekas dalam Pembuatan Media Pembelajaran - Hanafi, Ardi Nur; Septiwi, Ervina; Rahman, Nur Anisa; Citra, Yunsa; Maharani, Silva; Depra, Lola (YASIN, 2022)
Learning media plays an important part in teachings. However, if there is no learning media, the teaching activity will still continue to run but the results will be less than the maximum. The less maximum teaching activity that goes without learning media result from the limits of educationalists' delivery of information. For that reason, learning media is better to use in teaching activity for maximum results. Learning media has a various form and function. Learning media could be anything that can be used to help educationalists in presenting study materials or knowledge. In this study the research talks about the utilization of used items in the manufacture of learning media. in the manufacture of learning media, there is 2 process, The reuse of used items and scrap recycling. The recycling activity in order manufacturing of learning media can be costumized according to the learning's needs. The needs are teacher's ability, student's ability, and also the conformance to the study materials. Learning media that made by used items are made in such a way to meet the requirements to become the worth using learning media.